Serum Total Tryptase Level Confirms Itself as a More Reliable Marker of Mast Cells Burden in Mast Cell Leukaemia (Aleukaemic Variant). (10th February 2015) - Savini, P.; Rondoni, M.; Poletti, G.; Lanzi, A.; Quercia, O.; Soverini, S.; De Benedittis, C.; Musardo, G.; Martinelli, G.; Stefanini, G. F.
Abstract : Mast cell leukemia (MCL) is a very rare form of systemic mastocytosis (SM) with a short median survival of 6 months. We describe a case of a 65-year-old woman with aleukaemic variant of MCL with a very high serum total tryptase level of 2255  μ g/L at diagnosis, which occurred following an episode of hypotensive shock. She fulfilled the diagnostic criteria of SM, with a bone marrow smear infiltration of 50–60% of atypical mast cells (MCs). She tested negative for the KIT D816V mutation, without any sign of organ damage (no B- or C-findings) and only few mediator-related symptoms. She was treated with antihistamine alone and then with imatinib for the appearance of anemia. She maintained stable tryptase level and a very indolent clinical course for twenty-two months; then, she suddenly progressed to acute MCL with a serum tryptase level up to 12960  μ g/L. The patient died due to haemorrhagic diathesis twenty-four months after diagnosis. This clinical case maybe represents an example of the chronic form of mast cell leukemia, described as unpredictable disease, in which the serum total tryptase level has confirmed itself as a reliable marker of mast cells burden regardless of the presence of other signs or symptoms.